2009
DOI: 10.1021/pr800850a
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-Based Identification of Differentially-Expressed Proteins Including Galectin-1 in the Blood Plasma of Type 2 Diabetic Patients

Abstract: Type 2 diabetes (T2D) is a very heterogeneous and multifactorial disease. The pathophysiology of T2D is presumed to occur with an alteration in the levels of plasma proteins. To identify these differentially expressed proteins, plasma samples from normal and T2D humans were subjected to two-dimensional gel electrophoresis, quantitative densitometry, and mass spectrometry. Up to 200 protein spots were visible on each gel, of which 57 appeared modulated in diabetic individuals. Subsequently, 31 spots with > or =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 32 publications
3
28
1
1
Order By: Relevance
“…As reported previously by Xiao Junliu et al, galectin-1 was increased 4.8 times in Type 2 diabetic patients compared with normal individuals and a dose-dependent treatment of rat skeletal muscle cells with glucose resulted in an up-regulation of galectin-1 [16]. Similarly, we found that galectin-1 expression is a little higher in Type 1 diabetic mice than in normal mice (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As reported previously by Xiao Junliu et al, galectin-1 was increased 4.8 times in Type 2 diabetic patients compared with normal individuals and a dose-dependent treatment of rat skeletal muscle cells with glucose resulted in an up-regulation of galectin-1 [16]. Similarly, we found that galectin-1 expression is a little higher in Type 1 diabetic mice than in normal mice (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…This immunopharmacological profile of APS may be related to its beneficial effects in diseases with Th1/Th2 cytokine ratio imbalance, such as T1DM. Although APS may improve the metabolism of streptozotocin (STZ)-induced diabetic rats [14], enable insulin-sensitizing and anti-hyperglycemic activity in fat-fed STZ-treated rats [15], and delay onset of T1DM in NOD mice pretreated with APS [16], the mechanisms for improved hyperglycemia associated with APS may be multifaceted and at present remain unclear. Therefore, the purpose of our study was to investigate the therapeutic effects of APS on T1DM and elucidate the immunotherapeutic molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mass spectroscopic analysis of differentially expressed proteins in the plasma of Type II diabetic patients revealed a 4.8-fold increase in galectin-1 protein (22). Galectin-1 also binds the neuropilin-1 receptor on the surface of endothelial cells leading to the increased phosphorylation of the VEGFR-2 co-receptor, which activates the stress-activated protein kinase-1/c-Jun NH 2 -terminal kinase signaling pathway (11) and could influence angiogenesis in diabetic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…One of these, a-1-antitrypsin, was also identified in the recent diabetes urine proteome analyses as being increased in diabetic patients relative to controls but was not found to be specific to T2D in comparison to T1D (84). Fewer proteins were identified in the plasma proteome study of T2D, which used a 2DGE and MALDI-MS approach; however, the galectin-1 protein found and confirmed by ELISA to be significantly upregulated was also found to be induced by glucose in skeletal muscle cells (88). In summary, these studies demonstrate the usefulness of proteomic analysis of biological fluids for identifying novel candidate biomarkers and molecular mechanisms of pathogenesis in chronic disease.…”
Section: Proteomic Applications In Nutritionmentioning
confidence: 95%
“…This later study both validated a set of markers for distinguishing diabetic patients and identified markers capable of differentiating T2D and T1D, although an acknowledged weakness of this study was the variation in the clinical characteristics of each sample group. Additional research has focused on the salivary (87) and plasma (88) proteomes of T2D patients. Using label-free quantitation and multidimensional LC-MS/MS with significant fractionation, Rao et al (87) identified a notable 487 salivary proteins, of which 65 were differentially expressed in T2D.…”
Section: Proteomic Applications In Nutritionmentioning
confidence: 99%